The Mitigating Effect of Citrullus colocynthis (L.) Fruit Extract against Genotoxicity Induced by Cyclophosphamide in Mice Bone Marrow Cells - Mohammad Shokrzadeh; Aroona Chabra; Farshad Naghshvar; Amirhossein Ahmadi (The Scientific World Journal)
Possible genoprotective effect of Citrullus colocynthis (L.) (CCT) fruits extract against cyclophosphamide- (CP-)induced DNA damage in mice bone marrow cells was evaluated using micronucleus assay, as an index of induced chromosomal damage. Mice were preadministered with different doses of CCT via intraperitoneal injection for 7 consecutive days followed by injection with CP (70 mg/kg b.w.) 1 hr after the last injection of CCT. After 24 hr, mice were scarified to evaluate the frequency of micronucleated polychromatic erythrocytes (MnPCEs). In addition, the number of polychromatic erythrocytes (PCEs) among 1000 normochromatic erythrocytes (NCEs) per animal was recorded to evaluate bone marrow. Pretreatment with CCT significantly reduced the number of MnPCEs induced by CP in bone marrow cells (P<0.0001). At 200 mg/kg, CCT had a maximum chemoprotective effect and reduced the number of MnPCEs by 6.37-fold and completely normalized the mitotic activity. CCT also led to marked proliferation and hypercellularity of immature myeloid elements after mice were treated with CP and mitigated the bone marrow suppression. Our study revealed that CCT has an antigenotoxic effect against CP-induced oxidative DNA damage in mice. Therefore, it could be used concomitantly as a supplement to protect people undergoing chemotherapy.